"I Was a Game or a Fetish Object": Diverse Bisexual Women's Sexual Assault Experiences and Effects on Bisexual Identity. Issue 2 (18th August 2021) - Watson, Laurel B.; Craney, Raquel S.; Greenwalt, Sydney K.; Beaumont, Marcella; Whitney, Cassandra; Flores, Mirella J.
Abstract: Utilizing minority stress theory and intersectionality framework, this qualitative content analysis explored sexual assault experiences among 532 diverse bisexual women and gender expansive people. Findings revealed that many participants attributed their experiences of sexual assault to binegativity, which manifested as hypersexualization, "corrective rape, " perpetrator insecurity, and interpersonal hostility. In addition, participants described intersections between binegativity and other forms of oppression, including gendered racism, gendered binegativity, ableism, sizeism, and classism, and shared how they believed that these intersecting forms of oppression made them more vulnerable to sexual assault. Participants also described the ways in which sexual assault affected their understanding of and experience with their bisexual identity. For example, many participants expressed a number of relational and sexual affects (e.g., greater caution when entering into relationships with people of a certain gender, sexual discomfort, decreased sexual agency) and effects on their bisexual identity (e.g., identity disclosure process, questions about multiple aspects of their identities). Suggestions for future research and practice implications are discussed.